How urban green infrastructure contributes to carbon neutrality - Ranja Hautamäki; Liisa Kulmala; Mari Ariluoma; Leena Järvi (Buildings & Cities, 2025)
Reaching the carbon-neutrality targets of cities necessitates not only reducing emissions but also enhancing carbon sinks. This is enabled by urban green infrastructure (UGI), which is a cost-effective sink that provides numerous co-benefits beyond carbon sequestration. To fully harness this potential, it is essential to preserve existing carbon storage in urban planning, to create new multifunctional sinks, and to adopt low-emission practices in the construction and management of UGI. Key findings • Urban vegetation and soils provide a cost-efficient method of carbon sequestration and storage (CSS) that can be used more efficiently. • In addition to CSS, UGI provides other co-benefits: it helps to alleviate urban flooding and heatwaves and enhances biodiversity and wellbeing. • There are three key elements to harnessing UGI for adapting and mitigating climate change: preserving existing carbon stocks in UGI; creating new multifunctional carbon sinks; and adopting low-carbon practices and design options.